PERANAN PEJABAT LELANG KELAS II DALAM PELAKSANAAN LELANG DI INDONESIA - Diah Sulistyani Ratna Sediati (Masalah-Masalah Hukum, 2010)
Based on regulation of Finance Minister No: 119/PMK.07/2005 about Auctioneer Class II, the definition of Auctioneer Class ti is a person who is specially given an authority by Finance Minister to conduct the sale of the goods by auction way relied on the order of the Auction House as the authority of the sale of the goods' owner who is located in the Office of Auctioneer Class II The Auctioneer Class II is promoted and dismissed by The General Director on behalf of Finance Minister. The auctioneer is demanded to do injustice and does not take sides, so, his role must reflect a sense of justice and a certainty of law. Therefore, The auctioneer should take apart to support an effort of Law Enforcement in civil law, tax law, state administration law, and law of state asset management. The certainty of law is related to Authentic Act which is made by the auctioneer as the instrument of the most pertect evidence. The certainty of law is only able to occur if the auctioneers especially The Auctioneer Class II posses a high dignity and moral, a deep knowledge, and a skill of law and auction so that he can run his job fairly, strictly and consequently, autonomously non-sided, never-having dual job beyond his authority, keeping the importance of all the parties. The implementation of auction has to give a protection of law for those who have the same interest. Every implementation of auction must be made the report of the auction by the auctioneer as the authentic act. The report of auction is used to defend the seller or the goods' owner, the purchaser and the auctioneer to defend and to implement his right and responsibility